7th International Conference on Image Formation in X-Ray Computed Tomography 2022
DOI: 10.1117/12.2647158
|View full text |Cite
|
Sign up to set email alerts
|

Practical workflow for arbitrary non-circular orbits for CT with clinical robotic C-arms

Abstract: Non-circular orbits in cone-beam CT (CBCT) imaging are increasingly being studied for potential benefits in field-of-view, dose reduction, improved image quality, minimal interference in guided procedures, metal artifact reduction, and more. While modern imaging systems such as robotic C-arms are enabling more freedom in potential orbit designs, practical implementation on such clinical systems remains challenging due to obstacles in critical stages of the workflow, including orbit realization, geometric calib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] In recent years, non-circular scan orbits have been increasingly investigated for potential benefits such as increased field of view (FOV), [9][10][11][12] improved image quality and/or dose reduction, 7,[12][13][14][15] collision avoidance, 14,16 accom-modating upright patient positions [17][18][19] and reduced metal artifacts. 10,[20][21][22][23][24][25][26][27][28] While studies have demonstrated sufficient reproducibility for standard circular scanning orbits, [29][30][31][32] current implementations of non-circular orbits often result in a less predictable geometry due to factors such as gantry jitters, sagging, and manual data acquisition, and so forth. 8,12,[24][25][26][27]33,34 Since an accurate CBCT geometry is critical for the image quality of 3D reconstructions, we require a geometric calibration method that can address these challenges in practical implementations of non-circular or...…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3][4][5][6][7][8] In recent years, non-circular scan orbits have been increasingly investigated for potential benefits such as increased field of view (FOV), [9][10][11][12] improved image quality and/or dose reduction, 7,[12][13][14][15] collision avoidance, 14,16 accom-modating upright patient positions [17][18][19] and reduced metal artifacts. 10,[20][21][22][23][24][25][26][27][28] While studies have demonstrated sufficient reproducibility for standard circular scanning orbits, [29][30][31][32] current implementations of non-circular orbits often result in a less predictable geometry due to factors such as gantry jitters, sagging, and manual data acquisition, and so forth. 8,12,[24][25][26][27]33,34 Since an accurate CBCT geometry is critical for the image quality of 3D reconstructions, we require a geometric calibration method that can address these challenges in practical implementations of non-circular or...…”
Section: Introductionmentioning
confidence: 99%
“…10,[20][21][22][23][24][25][26][27][28] While studies have demonstrated sufficient reproducibility for standard circular scanning orbits, [29][30][31][32] current implementations of non-circular orbits often result in a less predictable geometry due to factors such as gantry jitters, sagging, and manual data acquisition, and so forth. 8,12,[24][25][26][27]33,34 Since an accurate CBCT geometry is critical for the image quality of 3D reconstructions, we require a geometric calibration method that can address these challenges in practical implementations of non-circular orbits. Specifically, the method should require no auxiliary instruments, accommodate non-circular geometries, provide frameby-frame geometric parameters to address frame-wise jitters,and be fast enough for the intraoperative workflow.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations